DO YOU PREFER STOCKS FOR YOUR PENSION PORTFOLIO? (American Journal of Business Management, Economics and Banking, 2025)
In this paper, we will try to investigate the pension preferences, how demographic and financial factors affect pension allocation using Binomial Logit Model. The dataset includes variables such as age, education, income, wealth, and stock investments, marital status, race, years in pension. The key questions explored are how factors like age, pension in years, education, wealth, profit sharing plan and investment choice influence pension decisions, mainly trying to capture the effects on the inclusion of stock investments in the pension portfolio. Since stocks are considered risky assets, this paper tries to represent the inclusion of stocks into the portfolio as the determinant of the risk aversion during the pension plan.